Community Based Cross- Sectional Study to Assess the Utilization Pattern of Antenatal Health Care Services among Married Women of Reproductive Age Group in a Rural Area of Bihar - Arvind Kumar Vimal; Pankaj Kumar (Asian Journal of Medical Research, 2020)
Background: ANC services is important to ensure safe motherhood. The present study was conducted to assess the utilization of ANC services in rural area.Subjects and Methods:The present study was community based cross-sectional in nature conducted upon 180 currently married women having children of less than one year of age and living in the area covered by rural training center of the institute. Sociodemographic profile and details of utilization of ANC services were noted.Results:Most of the respondents belonged to the age group of 20-30 years. 37.2% of them were illiterate and 58.9% lived in nuclear family. 53.9% had institutional delivery and 42.2% had more than two children. 42.8% of mothers registered their pregnancy before 12 weeks. Only 17.2% mothers had four or more ANC visits. 87.2% of them were fully immunized against tetanus but only 11.1% consumed 100 or more IFA tablets. Lack of awareness was responsible in 28.2%, lack of transport in 16.8%, unwillingness in 34.2% and other reasons in 20.8% cases among the mothers not utilizing ANC services properly.Conclusion: Utilization of ANC services is poor in this area.